Hur tränas hundar inom svenska brukshundklubbar? - Lindberg, Malena (SLU/Dept. of Animal Environment and Health (until 231231), 2007)
This is a descriptive paper based on a questionnaire- and literature study regarding how dogs are trained, what type and frequency of injuries that occur as well as how the dogs are best prepared for work. Using the results from the questionnaire, an overview is given on how members of Working dog clubs train their dogs and what kind of injuries that occur most frequently. The average age among the dogs included in the study was only about three years. This could indicate that older dogs are not trained in the same extent as young dogs. The results show that only a third of the dog owners warmed up their dogs before training. About fifty percent of the dog owners used massage and stretching on their dogs and most of them were self learned. Half of the dogs in the study had been injured at least one time. Preventive strategies for decreasing sport injuries and for obtaining the dog's health are discussed.